Driving Employee Performance in Hybrid Work Environments: The Role of Engagement, Support, Trust, and Respect - Wahyutomo, Dito; Hakim, Lukman; Oktayani, Dewi (PT. Riset Press International, 2025)
The COVID-19 pandemic has prompted many organizations to shift to a hybrid work model, which combines working from home and the office. This model is not just a temporary response but has become integral to long-term strategies. In an organizational context, companies that successfully implement this model show higher levels of employee engagement and better performance. Organizational support, trust, and respect for employees contribute significantly to work engagement and performance. This study used a quantitative approach with 131 respondents to evaluate the relationship between organizational support and work engagement. Results show that strong organizational support increases employee engagement, which in turn has a positive impact on individual performance.